Structure of a bacterial ribonucleoprotein complex central to the control of cell envelope biogenesis. (12th December 2022) - Islam, Md Saiful; Hardwick, Steven W; Quell, Laura; Durica‐Mitic, Svetlana; Chirgadze, Dimitri Y; Görke, Boris; Luisi, Ben F
Abstract: Biogenesis of the essential precursor of the bacterial cell envelope, glucosamine‐6‐phosphate (GlcN6P), is controlled by intricate post‐transcriptional networks mediated by GlmZ, a small regulatory RNA (sRNA). GlmZ stimulates translation of the mRNA encoding GlcN6P synthtase in Escherichia coli, but when bound by RapZ protein, the sRNA becomes inactivated through cleavage by the endoribonuclease RNase E. Here, we report the cryoEM structure of the RapZ:GlmZ complex, revealing a complementary match of the RapZ tetrameric quaternary structure to structural repeats in the sRNA. The nucleic acid is contacted by RapZ mostly through a highly conserved domain that shares an evolutionary relationship with phosphofructokinase and suggests links between metabolism and riboregulation. We also present the structure of a precleavage intermediate formed between the binary RapZ:GlmZ complex and RNase E that reveals how GlmZ is presented and recognised by the enzyme. The structures provide a framework for understanding how other encounter complexes might guide recognition and action of endoribonucleases on target transcripts, and how structured substrates in polycistronic precursors may be recognised for processing by RNase E. Synopsis: Biogenesis of the bacterial cell envelope and other complex metabolic processes are critically dependent on amino‐sugar metabolism, which is highly regulated at the post‐transcriptional level by RNA. Structural and in vivo analyses show how the key regulatory GlmZ small RNA is recognised by RapZ carrier protein, and how the RNA is presented for a highly specific, inactivated cleavage by a partner ribonuclease. The cryoEM structure of the binary complex of RNA carrier RapZ with small regulatory RNA GlmZ reveals details of recognition CryoEM shows how the GlmZ RNA is presented by RapZ protein for cleavage by endoribonuclease RNase E The models indicate how metabolites might interact with RapZ to modulate their regulation The structural data reveal a new RNA‐binding mode for an RNase E substrate capture, which may account for the recognition of other regulatory RNAs Abstract : The CryoEM structure of an sRNA‐protein complex provides insight into the regulation of bacterial cell wall synthesis.